Early Detection and Prevention of Skimming in Digital Financial Systems: A Forensic Accounting Approach in the Era of Technological Transformation (Lembaga Pengembangan Kinerja Dosen, 2025)
The advancement of digital technology in financial systems has brought significant convenience, but it has also introduced risks of cybercrimes such as skimming—the illegal theft of customer data. This study aims to explain how forensic accounting can assist in detecting and preventing skimming, particularly in cooperatives and small financial institutions that are vulnerable to such threats. The method used includes a literature review (2017–2025), as well as interviews and field observations. The findings indicate that skimming often occurs due to weak internal controls and a lack of staff awareness regarding digital security. Forensic accounting, through system log analysis and digital audit technology, has proven effective in detecting suspicious transaction patterns. Beyond technical approaches, Islam also emphasizes the importance of honesty in financial dealings and prohibits unjustly taking others’ property. As stated in the Qur’an (Surah Al-Baqarah, verse 188): “And do not consume one another’s wealth unjustly...” This study highlights that preventing skimming is not only a technological matter but also a moral and spiritual responsibility.